An anionic metal-organic framework as a platform for charge-and size-dependent selective removal of cationic dyes. (September 2018) - Zhao, Shu-Na; Krishnaraj, Chidharth; Jena, Himanshu Sekhar; Poelman, Dirk; Van Der Voort, Pascal
Abstract: A novel anionic framework {[Me2 NH2 ]0.5 [In0.5 L0.5 ]· x DMF}n (1 ) with two one-dimensional (1D) channels along the b axis of about 7.37 × 11.95 Å and 6.58 × 7.24 Å was solvothermally synthesized and characterized. The adsorption studies on organic dyes having different charges and sizes indicate that compound1 exhibits selective adsorption and separation behavior for cationic dyes through an ion-exchange process due to the presence of an intrinsic anionic framework. Additionally, compound1 can selectively separate methylene blue (MB + ) from the cationic dyes mixture consisting of methylene blue (MB + ) and rhodamine B (RhB + ). Moreover, when implemented as chromatographic column stationary phases, compound1 displays efficient and selective separation of MB + from both anionic-cationic dyes mixture and only cationic dyes mixture. Graphical abstract: An anionic MOF {[Me2 NH2 ]0.5 [In0.5 L0.5 ]· x DMF}n with two one-dimensional channels along the b axis of about 7.37 × 11.95 Å and 6.58 × 7.24 Å was successfully synthesized and built a platform for charge-and size-dependent selective separation of methylene blue used as the chromatographic column stationary phase. Highlights: An anionic MOF with two one-dimensional channels was synthesized. Selective adsorption behavior was monitored by VU-Vis spectroscopy. The ion exchange adsorption mechanism was discussed in detail. The anionic MOFs were used as the chromatographic column stationary phase.